Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.05.05.078568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repeated genomic signatures of adaptation to urbanisation in a songbird across Europe

Abstract: Urbanisation is currently increasing worldwide, and there is now ample evidence of phenotypic changes in wild organisms in response to this novel environment, but the extent to which this adaptation is due to genetic changes is poorly understood. Current evidence for evolution is based on localised studies, and thus lacking replicability. Here, we genotyped great tits (Parus major) from nine cities across Europe, each paired with a rural site, and provide evidence of repeated polygenic responses to urban habit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 59 publications
4
15
0
Order By: Relevance
“…Besides, the gene ontology enrichment analysis, performed on the entire set of genes identified via the outlier genome scan, reinforced these findings since multiple enriched GO terms were associated with the nervous system and stress response as well as hormonal response. These results are informative on the type of traits involved in avian urban adaptation in cities and corroborate previous results from (22, 60, 61) suggesting that natural selection repeatedly acted on neuronal, behavioural and cognitive traits that could contribute to the phenotypic shifts described in urban great tits (i.e. more aggressive and exploratory birds, with higher breath rate: 62, 63 & Caizergues et al in prep )…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Besides, the gene ontology enrichment analysis, performed on the entire set of genes identified via the outlier genome scan, reinforced these findings since multiple enriched GO terms were associated with the nervous system and stress response as well as hormonal response. These results are informative on the type of traits involved in avian urban adaptation in cities and corroborate previous results from (22, 60, 61) suggesting that natural selection repeatedly acted on neuronal, behavioural and cognitive traits that could contribute to the phenotypic shifts described in urban great tits (i.e. more aggressive and exploratory birds, with higher breath rate: 62, 63 & Caizergues et al in prep )…”
Section: Discussionsupporting
confidence: 89%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted February 10, 2021. ; https://doi.org/10.1101/2021.02.10.430452 doi: bioRxiv preprint to be greater in urban areas than in any other habitat types, including non-urban anthropogenic contexts (18,19). The exploration of the molecular mechanisms implicated in urban-driven phenotypic changes has only begun, with both genetic (20)(21)(22), and epigenetic investigations (23)(24)(25). For instance, DNA methylation variations have been associated in vertebrates with high levels of traffic-related air pollution (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, we have only touched on haplotype-based methods to infer adaptation here, and this will be the subject of future work. Environmental association approaches are also highly suited to detecting adaptation in widespread continental species [71,72], and further work will test how variation in the environment has shaped patterns of genomic variation in great tits [73]. This combination of environmental and genomic data in species such as great tits, in which a wealth of ecological and genomic resources are available, is likely to generate interesting insights into the the genetic and phenotypic basis of natural selection.…”
Section: Genomic Landscapes Of Differentiationmentioning
confidence: 99%
“…Genomic and epigenomic studies offer great potential to understand evolution in cities, yet they remain few and far between (Rivkin et al, 2019;Schell, 2018). While some studies have found genomic signatures of urban adaptation (Harris et al, 2013;Salmón et al, 2020) and consistent differences at the transcriptomic level (Watson et al, 2017), others have found no genetic structure among urban and nonurban congeners (Khimoun et al, 2020). Modifications in DNA methylation have been shown to associate with anthropogenic-linked factors including feeding on anthropogenic-provided food in baboons (Lea et al, 2016), exposure to pollution in humans (Baccarelli et al, 2009), and stress resilience in response to handling in tree swallows (Taff et al, 2019).…”
Section: Introductionmentioning
confidence: 99%